A ANALISA PERANCANGAN PERBAIKAN KUALITAS DENGAN PENDEKATAN TAGUCHI MELALUI PERSPEKTIF QUALITY CONTROL CIRCLE DAN QUALITY LOSS FUNCTION (Studi Kasus UD. Karya Logam Pandean) - Suparto; Fajrin, Achmad Farouq (Program Studi Teknik Industri Universitas Pembangunan Nasional Veteran Jawa Timur, 2024)
The purpose of this research is to analyze the design of quality improvement using the Taguchi approach through the perspective of quality control circles and quality loss function with a case study of the bucket conveyor production process at UD. Karya Logam Pandean. The bucket conveyor production process at UD. Karya Logam Pandean still has a high defect rate because it has not implemented good quality control and there are no standard production standards, which has resulted in quality losses for the company. The expected results of this research are to identify the dominant causes of defects and provide recommendations for improvement, to identify quality losses and propose an optimal design composition to reduce product defects. Data collection was carried out by conducting interviews and direct observations in the production area. This research shows that scratches are the dominant defect on bucket conveyor products with the main cause being the factor of the method and recommendations for improvement are obtained to standardize all production processes. This research also shows that the quality loss experienced by the company is Rp19,268/unit with an average daily loss of Rp163,778 and the optimal design composition to reduce defects is level 3, 2, 1 and 2.